Riwayat Ahli Bait Di Dalam Dunia Tafsir (Studi Komparasi Antara Tafsir Ar-Riwâ’i Dan Tafsir Bi Al-Ma’tsûr) - Fuqohak, MA. Zuhurul (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2019)
This study aims to find the position of the history of the temple experts of the Prophet. In the tradition of Sunni and Syi’ah scholarship. By using a comparative study between ar-riwâ'i interpretation used by Shiites and bi al-ma'tsûr interpretation used by Sunni. Research that uses qualitative, literature-based and analytical research methods finds that the history of the temple expert gets an extraordinary place and portion in the two circles. It was also found that the location of the similarities between Sunni-Syi’ah in the history of temple experts was equally accepted with several conditions. While the differences between the two are ar-riwâi interpretation only come from the Qur'an, the Prophet's hadithand the history of the temple expert. While the interpretation of bi al-ma'tsûr also uses the companions of the Prophet and tabi'in besides the three sources